Trends in multiple myeloma presentation, management, cost of care, and outcomes in the Medicare population: A comprehensive look at racial disparities. Issue 8 (23rd January 2018) - Ailawadhi, Sikander; Frank, Ryan D.; Sharma, Mayank; Menghani, Richa; Temkit, M'hamed; Paulus, Shumail; Khera, Nandita; Hashmi, Shahrukh; Advani, Pooja; Swaika, Abhisek; Paulus, Aneel; Aslam, Nabeel; et al.
Abstract : BACKGROUND: Outcomes have improved significantly in multiple myeloma (MM), but racial disparities in health care access and survival exist. A comprehensive analysis exploring MM care and racial disparities is warranted. METHODS: Patients with MM from 1991 to 2010 in the Surveillance, Epidemiology, and End Results‐Medicare database were evaluated for racial trends in clinical myeloma‐defining events (MDEs), the receipt of treatment (drugs and stem cell transplantation; [SCT]), the cost of care, and overall survival (OS). RESULTS: Among 35, 842 patients, the frequency of all MDEs at diagnosis increased over time; whereas, in recent years (2006‐2010), all MDEs with the exception of renal dialysis decreased. Blacks had highest rates for all MDEs except bone fractures, which were highest in whites. Over time, the proportion of patients who received any treatment, multiple agents, and SCT increased significantly, and the largest increase was observed in the receipt of immunomodulatory drugs and steroids. There was greater receipt of bortezomib and SCT among whites and blacks and higher receipt of immunomodulatory drugs among Hispanics and Asians ( P < .001). Medicare claims were highest during first 6 months after MM diagnosis for blacks and at any time after MM diagnosis for Hispanics. Over time, Medicare claims increased most steadily for Hispanics ( P < .001). Hypercalcemia, renal dysfunction, and bone fractures were associated with inferior OS. Blacks and Asians had superior OS compared with whites, but racial differences in OS became less pronounced during 2006 through 2010 ( P = .182) compared with prior years ( P < .01). Better OS was noted among patients who had higher median incomes. CONCLUSIONS: The current results indicate that there have been significant changes in the management of patients with MM over time and provide an in‐depth understanding of the factors that may help explain racial disparities. Cancer 2018;124:1710‐21 . © 2018 American Cancer Society Abstract : Significant trends are reported for changes in the management of patients with multiple myeloma over 2 decades. The results provide an in‐depth understanding of factors that may help explain racial disparities in outcomes, including disease presentation, health care use, and the cost of care.